Development and initial validation of MedHipPro-Q: a questionnaire assessing medication management of hip fracture patients in different care settings - Ben Tore Henriksen; Yvonne Andersson; Maren Nordsveen Davies; Liv Mathiesen; Maria Krogseth; Randi Dovland Andersen (BMC, 2022)
Abstract Background A validated questionnaire to assess medication management of hip fracture patients within and outside the hospital setting was lacking. The study aims were to describe the hip fracture patient pathway, and develop a valid and feasible questionnaire to assess clinicians' experience with medication management of hip fracture patients in different care settings throughout the patient pathway. Methods This qualitative, descriptive methodological study used strategic and snowball sampling. The questionnaire was developed, and face and content validity explored through interviews with stakeholders. Phase I described the hip fracture patient pathway, and identified questionnaire dimensions in semi-structured interviews with management and clinicians (n = 37). The patient pathway was also discussed in six meetings (n = 70). Phase II refined a first draft of the questionnaire through cognitive interviews with future respondents (n = 23). The draft was modified after each interview. Post hoc, cognitive interview data were analysed using matrix analysis to condense problems and solutions into themes and subthemes. Phase III, converted the final version to a digital format, and tested its feasibility with a subset of the cognitive interview participants (n = 21) who completed the questionnaire and provided feedback. Results Phase I: Hip fracture patients were cared for in at least three different care settings, and went through at least four handovers between and within primary and secondary care. Three questionnaire dimensions were identified: 1) Medication reconciliation and review, 2) Communication of key information, and 3) Profession and setting. Phase II: The MedHipPro-Q was representative of how the different professions experienced medication management in all settings, and hence showed face and content validity. Post hoc analysis: Problem themes (with sub-themes) were Representativeness (-of patient pathway and -of respondent reality) and Presentation (Language and Appearance). Solution themes (with sub-themes) were: Content (added or deleted) and Presentation (modified appearance or corrected language). Phase III: Participants did not identify technical, linguistic or content flaws in the questionnaire, and the digital version was considered feasible for use. Conclusion The novel MedHipPro-Q showed good face and content validity, and was feasible for use throughout the hip fracture patient pathway. The rigorous development process supports its construct validity and reliability.